2011
DOI: 10.1111/j.1742-481x.2011.00797.x
|View full text |Cite
|
Sign up to set email alerts
|

Platelet‐rich plasma versus platelet‐poor plasma in the management of chronic diabetic foot ulcers: a comparative study

Abstract: Non healing diabetic foot ulcers and the resulting potential amputations present significant costs to the health care system and reduce patient quality of life. The goal of diabetic foot ulcer treatment is to obtain wound closure as expeditiously as possible. The use of platelet-rich plasma (PRP) to enhance wound healing has increased dramatically over the last decade. However, controversies exist in the literature regarding the added benefit of this procedure. The aim of this study is to investigate the effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
107
0
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(129 citation statements)
references
References 18 publications
4
107
0
7
Order By: Relevance
“…PRP e HA sono terapie capaci di dare sollievo ai pazienti affetti da OA, e potenzialmente di ridurre, o per lo meno ritardare, il ricorso all'intervento chirurgico di artroprotesi al ginocchio (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). Diversi studi mostrano che il PRP ha un'efficacia superiore all'HA (34)(35)(36)(37)(38)(39)(40)(41)(42).…”
Section: Discussioneunclassified
See 2 more Smart Citations
“…PRP e HA sono terapie capaci di dare sollievo ai pazienti affetti da OA, e potenzialmente di ridurre, o per lo meno ritardare, il ricorso all'intervento chirurgico di artroprotesi al ginocchio (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). Diversi studi mostrano che il PRP ha un'efficacia superiore all'HA (34)(35)(36)(37)(38)(39)(40)(41)(42).…”
Section: Discussioneunclassified
“…La provetta viene sottoposta a centrifugazione alla velocità di 1500 g (3400 rpm) per 5 minuti, il che consente di separare i globuli rossi (sotto il gel) dal plasma impoverito di piastrine (PPP) e il PRP (sopra il gel). Capovolgendo dolcemente e più volte la provetta BCT-1 si procede alla risospensione degli elementi cellulari nel surnatante e si ottiene il PRP (circa 4 ml), che può quindi essere prelevato mediante siringa sterile e infiltrato nell'articolazione del paziente (30,49).…”
Section: Costiunclassified
See 1 more Smart Citation
“…Although the efficacy of PRP has been investigated in wound healing [12][13][14][15] , its effects on TMP healing have not yet been investigated in acute TMPs. In the literature, the only study on the effect of PRP on TMP closure is that reported by El-Anwar et al [16] , wherein they studied 64 patients with chronic TMPs who had undergone postauricular myringoplasty with underlay graft using conchal perichondrial graft.…”
Section: Discussionmentioning
confidence: 99%
“…There have been human studies to report that PRP has a positive effect on wound healing [12][13][14][15] . In animal studies, histological examinations revealed enhanced fibroblastic and endothelial cell formation during wound healing, increased neovascularization [12,[19][20][21][22] , and enhanced granulation tissue formation [12,19,21,22] .…”
Section: Discussionmentioning
confidence: 99%